SIZING OF DRAINAGE SYSTEMS THROUGH COMPUTER SOFTWARE - LUDWIG, RAFAEL; SAAD, JOÃO C. C.; PUTTI, FERNANDO F.; JUNIOR, JOSUÉ F. DA S.; SCHIMIDT, ANA PAULA R. A.; LATORRE, DEBORA DE O.; SILVA, ILCA P. DE F. E (Revista Brasileira de Engenharia de Biossistemas, 2013)
On agricultural land, with drainage deficit, it is important to remove water excess by artificial devices, called drains, improving the aeration conditions and soils resistance and structure. However, to obtain an optimal functioning of the system, it is important to consider the factors involved, such as soil characteristics, culture, flow regime and the drainage criteria. To facilitate this process, a software was developed using the PASCAL language, based on Hooghoudt and Ernest equations for the steady-state condition, and the Glover-Dumm equations for the variable. Thus, for the drains design the user will have to decide which regime applies to each situation. After that, the soil profile is defined which can be homogeneous or divided into two layers, noting that arrangements for the variable flow considers constant the saturated soil hydraulic conductivity throughout the soil profile. It is also necessary to define the drain location above the barrier layer and the drain type, tubular or trapezoidal. Finally, after all the necessary data been informed the program could calculate the drain spacing quickly and accurately, meeting the needs of each drainage project.